Triatominae vectors of Chagas disease - Schofield, Christopher J. (Henry Stewart Talks, 2010)
History of Chagas disease including incidence, prevalence and economic impact, Classification, biology and ecology of Triatominae, Role as vectors, Population dynamics, Population genetics, Chagas disease control initiatives including background, progress and challenges
Reviewed at 2022/04/12